Prison memory in the Shining Path and the Tupumaro National Liberation Movement (1982-2017) - Encarnación Pinedo, Miriam (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The following study is written within the works of history of memory. It seeks to analyze how the prison memory of two subversive, leftist Latin American organizations created a whole discursive corpus based on political propaganda. The cornerstone of the construct is «the militant hero», which will be analyzed from the narrative reconstruction of the prison memory of both organizations. More concretely, this investigation aims to answer the following questions: what is the objective of these organizations in making an effort to rebuild a memory of confinement? Wouldn't this effort be contradictory, taking into account the Tupumaro National Liberation Movement political conquest and the Shining Path's plan to have a place in politics?  This comparative study intends to demonstrate that this construction intends to present a suprahuman image of the prisoners who belong to these two guerrilla groups and, also, an inhuman image of those who had to face them. All of the above, to denounce the reaction of the state through the words that were denied to them 40 years before, and of building, therefore, a memory that allows them to tell another version that fosters greater social acceptance and facilitates their political participation.